PEMBELAJARAN DALAM MENINGKATKAN KECERDASAN EMOSIONAL SANTRI BERBASIS TOTAL QUALITY MANAGEMENT DI PESANTREN - Samsudin, Cucu; Rukanda, Nandang (Comm-Edu (Community Education Journal), 2024)
The order of human life in the hierarchy of character has a lot of decline in the values of morality and discipline, which results in low morals and a loss of manners. The increasingly advanced conditions of technology have encouraged the development of intellectual intelligence with technical knowledge but ironically with the understanding of religious knowledge. In fact, religious knowledge can influence the formation of human character through psychomotorism. His cognition is filled with religious knowledge and his affection is filled with faith. Psychomotor skills are the most important biological part of the process of forming morals through character education. By using the Islamic boarding school learning model in the form of a total quality management model. The aim is to improve the quality of educational products so that they achieve results that comply with quality standards. The expected indicator in Islamic boarding school education is to have a standard standard of quality achievement in the form of noble morals.